2022
DOI: 10.1002/vms3.877
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude of calf morbidity and mortality and risk factors in smallholder farms across livestock production systems in central Ethiopia

Abstract: Background Calf morbidity and mortality are major constraints in Ethiopian cattle production that severely limit available replacement stock. Calf morbidity and mortality reports in Ethiopia mostly focus on market‐oriented dairy production systems. A cross‐sectional study was undertaken in central Ethiopia with the objectives of estimating the magnitude of calf morbidity and mortality across three production systems and contributing risk factors. Methods A cross‐sectional study was conducted at pastoral, mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…It accounted for 71.3% of all morbidity and 62.1% of all mortalities. Similar to the current data, other authors in Ethiopia have identified that diarrhea and pneumonia are the two most significant health issues affecting calves [11,[15][16][17][18]33]. In studies conducted outside Ethiopia, the two disease conditions were likewise included as the primary and secondary causes of calf morbidity and mortality [34,35].…”
Section: Discussionsupporting
confidence: 71%
“…It accounted for 71.3% of all morbidity and 62.1% of all mortalities. Similar to the current data, other authors in Ethiopia have identified that diarrhea and pneumonia are the two most significant health issues affecting calves [11,[15][16][17][18]33]. In studies conducted outside Ethiopia, the two disease conditions were likewise included as the primary and secondary causes of calf morbidity and mortality [34,35].…”
Section: Discussionsupporting
confidence: 71%
“…Diarrhea accounted for 71.3% of overall morbidities and 62.1% of all mortalities. Similar to the current data, other authors in Ethiopia have identi ed that diarrhea and pneumonia are the two most signi cant health issues affecting calves [11,[14][15][16][17]31]. In studies conducted outside Ethiopia, the two disease conditions were likewise included as the primary and secondary causes of calf morbidity and mortality [32,33].…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, they pose a signi cant potential threat to both breeders and livestock 23 . In addition, they can cause growth retardation, immune de ciency, organ dysfunction, and even death by poisoning 24,25 . Moreover, their release into the external environment can result in environmental pollution 26 .…”
Section: Concentrations Of Airborne Culturable Bacteria Fungi and Ent...mentioning
confidence: 99%